2021
DOI: 10.1111/nyas.14711
|View full text |Cite
|
Sign up to set email alerts
|

Interbrain emotional connection during music performances is driven by physical proximity and individual traits

Abstract: How musical emotions and the pleasure derived from music, regardless of the musical valence, can be shared between individuals is a fascinating question, and investigating it can shed light on the function of musical reward. We carried out our investigations in a natural setting during an international competition for orchestra conductors. Participants (n = 15) used a dedicated smartphone app to report their subjective emotional experiences in real time while we recorded their cerebral activity using electroen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 86 publications
2
37
0
Order By: Relevance
“…The total interdependence (TI) method was employed to calculate the inter-brain coupling by computing the magnitude squared coherence between brain signals simultaneously recorded from two students 27,28,52 . This method has been previously used in inter-brain studies to investigate individuals’ engagement and valence level in naturalistic scenarios such as a classroom and a concert hall 27,53 . To test our hypothesis, student-class coupling and student-excellence coupling were calculated for each student as indicators of the disciplinary learning process for the whole semester, as shown in Fig.3 b, c .…”
Section: Resultsmentioning
confidence: 99%
“…The total interdependence (TI) method was employed to calculate the inter-brain coupling by computing the magnitude squared coherence between brain signals simultaneously recorded from two students 27,28,52 . This method has been previously used in inter-brain studies to investigate individuals’ engagement and valence level in naturalistic scenarios such as a classroom and a concert hall 27,53 . To test our hypothesis, student-class coupling and student-excellence coupling were calculated for each student as indicators of the disciplinary learning process for the whole semester, as shown in Fig.3 b, c .…”
Section: Resultsmentioning
confidence: 99%
“…Researchers are increasingly foregoing ultimate control for a more ecologically valid approach that enables participants to have more powerful aesthetic experiences. This study follows others that have moved more into the 'wild' to explore such naturalistic experiences (Chabin et al, 2022;Czepiel et al, 2021;Dotov & Trainor, 2021;Merrill et al, 2021;Swarbrick et al, 2019;Tervaniemi et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…However, this enhanced AE effect has been mostly assessed in laboratory settings. Recent studies are increasingly exploring such experiences in live concerts (Chabin et al, 2022; Czepiel et al, 2021; Merrill et al, 2021; Scherer et al, 2019; Swarbrick et al, 2019; Tervaniemi et al, 2021), where participants report to experience stronger emotions (Gabrielsson & Wik, 2003; Lamont, 2011); though note that Belfi et al (2021) found that felt pleasure did not differ between live and an audiovisual recording of the same performance. Focusing more specifically on the role of modality, to date only a few studies compare responses to AV vs. AO conditions in naturalistic settings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations